MENELISIK DINAMIKA DAN EKSISTENSI FATWA MUI SEBAGAI UPAYA MITIGASI PANDEMI COVID-19 - Abdur Rahman Adi Saputera (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
ABSTRACTThis research is designed in the form of research (Library Research) using various sources of literature as a source of research data, with the aim of investigating and analyzing the values of the existence of the MUI Fatwa in an effort to mitigate Covid-19 which is becoming increasingly rampant. This study also applies a descriptive-normative approach because it is aimed at describing the pandemic and the existence of Fatwa as a real phenomenon, which gives birth to various dynamics and social responses in the community, and departs from the building of primary and secondary data sources as support, from the data collected through documents. which is inter-correlative and a review of social realities in society, the author tries to analyze it through the Descriptive Analytic Method Content process as an analysis knife. The results show that, in fact, the role and influence of the MUI fatwa during the pandemic as a form of mitigating Covid-19 are ideal and strategic steps. Even though at the beginning of its existence, the Pandemic Fatwa experienced various kinds of dynamics, such as conflicts and so on. But in the end, it got a responsive reaction from all circles, because in principle, the existence of the fatwa is an essential form of alternatives and solutions in creating a more progressive, realistic, dynamic, and contextualist religious and religious pattern, which at the same time displays the face of Islamic Law which is rahmatan lil. alamin sholihul likulli wal eat. Keywords: Dynamics, Existence, MUI Fatwa, Covid-19